Quantum walks with dynamical control: graph engineering, initial state preparation and state transfer - Nitsche, Thomas; Elster, Fabian; Novotný, Jaroslav; Gábris, Aurél; Jex, Igor; Barkhofen, Sonja; Silberhorn, Christine (New Journal of Physics)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Direct generation of genuine single-longitudinal-mode narrowband photon pairs - Luo, Kai-Hong; Herrmann, Harald; Krapick, Stephan; Brecht, Benjamin; Ricken, Raimund; Quiring, Viktor; Suche, Hubertus; Sohler, Wolfgang; Silberhorn, Christine (New Journal of Physics)

A population-competition model for analyzing transverse optical patterns including optical control and structural anisotropy - Tse, Y C; Chan, Chris K P; Luk, M H; Kwong, N H; Leung, P T; Binder, R; Schumacher, Stefan (New Journal of Physics)

Directly comparing entanglement-enhancing non-Gaussian operations - Bartley, Tim; Walmsley, Ian A (New Journal of Physics)

Direct generation of genuine single-longitudinal-mode narrowband photon pairs - Luo, Kai Hong; Herrmann, Harald; Krapick, Stephan; Brecht, Benjamin; Ricken, Raimund; Quiring, Viktor; Suche, Hubertus; Sohler, Wolfgang; Silberhorn, Christine (New Journal of Physics)

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A.; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Formation and interaction of resonance chains in the open three-disk system - Weich, T; Barkhofen, Sonja; Kuhl, U; Poli, C; Schomerus, H (New Journal of Physics)

Formation and interaction of resonance chains in the open three-disk system - Weich, Tobias; Barkhofen, Sonja; Kuhl, U; Poli, C; Schomerus, H (New Journal of Physics)
Keywords: General Physics and Astronomy

A source of polarization-entangled photon pairs interfacing quantum memories with telecom photons - Clausen, C; Bussières, F; Tiranov, A; Herrmann, Harald; Silberhorn, Christine; Sohler, W; Afzelius, M; Gisin, N (New Journal of Physics)
Keywords: General Physics and Astronomy

Three-dimensional hybrid vortex solitons - Driben, Rodislav; Kartashov, Yaroslav V.; Malomed, Boris A.; Meier, Torsten; Torner, Lluis (New Journal of Physics)
We show, by means of numerical and analytical methods, that media with a repulsive nonlinearity which grows from the center to the periphery support a remarkable variety of previously unknown complex stationary and dynamical three-dimensional (3D) solitary-wave states. Peanut-shaped modulation profiles give rise to vertically symmetric and antisymmetric vortex states, and novel stationary hybrid states, built of top and bottom vortices with opposite topological charges, as well as robust dynamical hybrids, which feature stable precession of a vortex on top of a zero-vorticity soliton. The analysis reveals stability regions for symmetric, antisymmetric, and hybrid states. In addition, bead-shaped modulation profiles give rise to the first example of exact analytical solutions for stable 3D vortex solitons. The predicted states may be realized in media with a controllable cubic nonlinearity, such as Bose–Einstein condensates.

Theory of quantum frequency conversion and type-II parametric down-conversion in the high-gain regime - Christ, Andreas; Brecht, Benjamin; Mauerer, Wolfgang; Silberhorn, Christine (New Journal of Physics)

An efficient integrated two-color source for heralded single photons - Krapick, S; Herrmann, Harald; Quiring, V; Brecht, Benjamin; Suche, H; Silberhorn, Christine (New Journal of Physics)

Aharonov–Bohm rings with strong spin–orbit interaction: the role of sample-specific properties - Nichele, F; Komijani, Y; Hennel, S; Gerl, C; Wegscheider, W; Reuter, Dirk; Wieck, A D; Ihn, T; Ensslin, K (New Journal of Physics)

Spatio-spectral characteristics of parametric down-conversion in waveguide arrays - Kruse, R; Katzschmann, F; Christ, A; Schreiber, A; Wilhelm, S; Laiho, K; Gábris, A; Hamilton, C S; Jex, I; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Entanglement quasiprobabilities of squeezed light - Sperling, Jan; Vogel, W (New Journal of Physics)

Exponentially enhanced quantum communication rate by multiplexing continuous-variable teleportation - Christ, Andreas; Lupo, Cosmo; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Characteristics of displaced single photons attained via higher order factorial moments - Laiho, Kaisa; Avenhaus, Malte; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

From quantum pulse gate to quantum pulse shaper—engineered frequency conversion in nonlinear optical waveguides - Brecht, Benjamin; Eckstein, Andreas; Christ, Andreas; Suche, Hubertus; Silberhorn, Christine (New Journal of Physics)

Probing multimode squeezing with correlation functions - Christ, Andreas; Laiho, Kaisa; Eckstein, Andreas; Cassemiro, Katiúscia N; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Multi-walker discrete time quantum walks on arbitrary graphs, their properties and their photonic implementation - Rohde, Peter P; Schreiber, Andreas; Štefaňák, Martin; Jex, Igor; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Observation of orientation- andk-dependent Zeeman spin-splitting in hole quantum wires on (100)-oriented AlGaAs/GaAs heterostructures - Chen, J C H; Klochan, O; Micolich, A P; Hamilton, A R; Martin, T P; Ho, L H; Zülicke, U; Reuter, Dirk; Wieck, A D (New Journal of Physics)

Optical probing of spin dynamics of two-dimensional and bulk electrons in a GaAs/AlGaAs heterojunction system - Rizo, P J; Pugzlys, A; Slachter, A; Denega, S Z; Reuter, Dirk; Wieck, A D; van Loosdrecht, P H M; van der Wal, C H (New Journal of Physics)

Accessing the purity of a single photon by the width of the Hong–Ou–Mandel interference - Cassemiro, Katiúscia N; Laiho, Kaisa; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Optimized generation of heralded Fock states using parametric down-conversion - Brańczyk, Agata M; Ralph, T C; Helwig, Wolfram; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Feasibility of free space quantum key distribution with coherent polarization states - Elser, D.; Bartley, Tim; Heim, B.; Wittmann, Ch; Sych, D.; Leuchs, G. (New Journal of Physics)
We demonstrate for the first time the feasibility of free space quantum key distribution with continuous variables under real atmospheric conditions. More specifically, we transmit coherent polarization states over a 100 m free space channel on the roof of our institute's building. In our scheme, signal and local oscillator (LO) are combined in a single spatial mode, which auto-compensates atmospheric fluctuations and results in an excellent interference. Furthermore, the LO acts as a spatial and spectral filter, thus allowing unrestrained daylight operation.

Quantum dot as thermal rectifier - Scheibner, R; König, M; Reuter, Dirk; Wieck, A D; Gould, C; Buhmann, H; Molenkamp, L W (New Journal of Physics)

Ab initio study of the half-metal to metal transition in strained magnetite - Friák, Martin; Schindlmayr, Arno; Scheffler, Matthias (New Journal of Physics)
Using density-functional theory, we investigate the stability of the half-metallic ground state of magnetite under different strain conditions. The effects of volume relaxation and internal degrees of freedom are fully taken into account. For hydrostatic compression, planar strain in the (001) plane and uniaxial strain along the [001] direction, we derive quantitative limits beyond which magnetite becomes metallic. As a major new result, we identify the bond length between the octahedrally coordinated iron atoms and their neighbouring oxygen atoms as the main characteristic parameter, and we show that the transition occurs if external strain reduces this interatomic distance from 2.06 Å in equilibrium to below a critical value of 1.99 Å. Based on this criterion, we also argue that planar strain due to epitaxial growth does not lead to a metallic state for magnetite films grown on (111)-oriented substrates.

Lagrangian structures and transport in turbulent magnetized plasmas - Padberg, Kathrin; Hauff, Thilo; Jenko, Frank; Junge, Oliver (New Journal of Physics)

Magnetization of bilayer two-dimensional electron systems - Bominaar-Silkens, I M A; Schaapman, M R; Zeitler, U; Christianen, P C M; Maan, J C; Reuter, Dirk; Wieck, A D; Schuh, D; Bichler, M (New Journal of Physics)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)